2014
DOI: 10.1111/ijlh.12190
|View full text |Cite
|
Sign up to set email alerts
|

FVIII and FIX inhibitors in people living with hemophilia in Cameroon, Africa: a preliminary study

Abstract: The frequency of inhibitors in hemophiliac patient undergoing replacement therapy is high in Cameroon. Severity of disease was found to be the main contributing factor in patients who developed inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 7 publications
1
8
1
Order By: Relevance
“…Data on inhibitors and molecular diagnosis in PWH are scarce in Sub-Saharan Africa. 15,16 This is the first prospective study in 17,18 We reported a similar distribution of intron 22 inversions, point variants and rearrangements compared to non-African ethnic groups. This distribution had previously been reported in studies from Senegal and South Africa.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Data on inhibitors and molecular diagnosis in PWH are scarce in Sub-Saharan Africa. 15,16 This is the first prospective study in 17,18 We reported a similar distribution of intron 22 inversions, point variants and rearrangements compared to non-African ethnic groups. This distribution had previously been reported in studies from Senegal and South Africa.…”
Section: Discussionmentioning
confidence: 61%
“…Finally, we compared our results on prevalence of inhibitor and genetic‐related risk factors for inhibitor development (if available with those obtained from other Sub‐Saharan African countries (Cameroon, Senegal and South Africa) and reported in peer‐reviewed journals.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, there is paucity of data on haemophilia and its management in Cameroon. To date, few available data report just over 100 diagnosed and registered cases [5]. The role of the WFH is to work together with national associations to promote the well-being of PLWH worldwide.…”
Section: Introductionmentioning
confidence: 99%